Adult Cochlear Implant Recipients’ Perspectives on Experiences With Music in Everyday Life: A Multifaceted and Dynamic Phenomenon - Gfeller, Kate; Driscoll, Virginia; Schwalje, Adam (Frontiers in Neuroscience, 2019)
Background: Cochlear implants (CIs), which have been designed primarily to support spoken communication of persons with severe to profound hearing loss, are highly effective in supporting speech perception in quiet listening conditions. CI users as a group achieve significantly poorer perception and appraisal of music, and speech perception is compromised when background music is present, thought outcomes vary considerably across recipients. A number of factors have been identified that contribute to variable music listening experiences, but many questions remain, particularly regarding experiences in everyday life from the perspective of CI users. Purpose: The purpose of this study was twofold: The first aim was to explore the perspectives of adult CI recipients regarding two experiences with music in everyday life: purposeful music listening and background music that competes with spoken conversation. The second aim was to develop a framework of everyday music experiences based upon CI perspectives that could inform future rehabilitative practices and research initiatives. Methods: Qualitative and patient-engaged research methodologies were used to emphasize the perspectives of the CI users. Participants included 40 experienced adult CI users ranging in age from 19 to 81 enrolled in 13 CI centers. Participants completed on-line semi-structured open-ended questionnaires regarding purposeful music listening and background music in conjunction with spoken communication. Responses were analyzed using an iterative inductive coding process consistent with grounded theory methodology. The interrelated themes that emerged from the data were then organized into a model synthesizing components from models on music response and self-management for persons with chronic health conditions. Outcomes: Data analyses informed the development of a Dynamic Problem Solving Model for Management of Music Listening Environments adapted from Hill-Briggs (2003) Problem Solving Model of Chronic Illness Self-Management. Key findings were: 1) Music listening is a dynamic, multifaceted experience; satisfactory listening depended upon optimal combinations of factors; 2) Music listening is effortful, but the extent of satisfaction is influenced by expectations and self-management of the situation; 3) CI users have limited access to resources for optimizing music experiences. Many CI users would consider rehabilitation, but level of commitment and priorities differ across CI users.